1989
DOI: 10.1002/cne.902800206
|View full text |Cite
|
Sign up to set email alerts
|

Central distribution of cervical primary afferents in the rat, with emphasis on proprioceptive projections to vestibular, perihypoglossal, and upper thoracic spinal nuclei

Abstract: The projections of primary afferents from rostral cervical segments to the brainstem and the spinal cord of the rat were investigated by using anterograde and transganglionic transport techniques. Projections from whole spinal ganglia were compared with those from single nerves carrying only exteroceptive or proprioceptive fibers. Injections of horseradish peroxidase (HRP) or wheat germ agglutinin-horseradish peroxidase conjugate (WGA-HRP) were performed into dorsal root ganglia C2, C3, and C4. Free HRP was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(74 citation statements)
references
References 82 publications
4
69
0
1
Order By: Relevance
“…ment C2/C3 are thought unlikely to be a cause of vertigo [27,28]. Clinical experience correlates with anatomical studies, which were able to identify links between cervical spine receptors and vestibular nuclei [1,2,[17][18][19]. A large supply of receptors was found in neck muscles, especially when muscles were short and in close proximity to facet joints [6].…”
mentioning
confidence: 49%
“…ment C2/C3 are thought unlikely to be a cause of vertigo [27,28]. Clinical experience correlates with anatomical studies, which were able to identify links between cervical spine receptors and vestibular nuclei [1,2,[17][18][19]. A large supply of receptors was found in neck muscles, especially when muscles were short and in close proximity to facet joints [6].…”
mentioning
confidence: 49%
“…Foremost, it is Fractional areas (FA), percentages of silver grains (%), and LDs in hypoglossal motoneuron cell bodies 8 and 15 h after tongue injections in neonatal rat pups crucial for our claim of retrograde transcytosis that we can rule out the possibility that the radioactive material could have arrived in afferent synapses by any route other than retrograde axonal transport. This is the case, because the rat tongue lacks proprioceptive afferent innervation (Neuhuber and Zenker, 1989), and there is no sensory monosynaptic pathway to the hypoglossal motor nucleus in rats (Fay and Norgren, 1997;Zhang et al, 2001). Thus, the circuitry of the hypoglossal model system chosen for this analysis allows us to draw conclusions that would not be possible in spinal or trigeminal motor circuits.…”
Section: The Hypoglossal Model Systemmentioning
confidence: 99%
“…This model system was chosen because hypoglossal motoneurons lack direct monosynaptic afferent proprioceptive input from the tongue (Neuhuber and Zenker, 1989;Fay and Norgren, 1997;Zhang et al, 2001), thus providing a "clean" retrograde transport model system devoid of any potential contamination of afferent synapses on motoneurons by anterograde (sensory) axonal transport. We compared the accumulation and transsynaptic transfer of BDNF, GDNF, CT-1, and tetanus toxin in the hypoglossal nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons with the distribution of central terminals seen after transganglionic labeling of trigeminal [Jacquin et al, 1983;Takemura et al, 1987], upper cervical [Pfaller and Arvidsson, 1988;Neuhuber and Zenker, 1989], or vagal afferent nerves [Contreras et al, 1982], suggested a high percentage of Fos-positive neurons produced at the dPa5 and Vc/C2 junction region resulted from direct input from primary afferent fibers. By contrast, Fos-LI produced at the Vi/Vc-vl transition region more likely represented third-or higher-order neurons since few primary afferent fibers project from the TMJ region to this brainstem area.…”
Section: Fos-li As a Marker For Primary Afferent Input From The Tmj Rmentioning
confidence: 99%